THE USE OF TECHNOLOGIES IN THE TEACHING AND LEARNING PROCESS IN EARLY EARLY EDUCATION - Carneiro de Lima, Valdeni; Rejane Brasileiro Costa, Ilmara; Lima Silva, Judivan; Dias da Silva, Damiana; Pereira de Caldas, Marinez; Paulo Pereira, Rosimary; das Graças da Silva Souza, Maria; do Socorro Almeida Angelo Segunda, Maria (Revista Gênero e Interdisciplinaridade, 2024)
Considered to be the true ‘door to the educational process’, it is clear that early childhood education needs to develop considering the use of technological resources in the classroom. This is because in today’s world, children have constant interaction with technology, developing skills in which they surpass adults. Therefore, there is no way to develop early childhood education without this type of resource. The non-inclusion of technologies in this educational modality constitutes an attempt to develop an educational process disconnected from reality. Regardless of the type of media used, technologies are important for early childhood education, as they are indispensable tools nowadays that, combined with the educator’s knowledge, provide children’s development. This is a bibliographical review with the aim of discussing the use of technologies in the teaching and learning process of early childhood education.